Acidometric Agar Plate Method for Ampicillin Susceptibility Testing of Haemophilus influenzae - Park, Choong H. (1978)
The need for an accurate and rapid method of testing ampicillin susceptibility of Haemophilus influenzae, especially strains isolated from patients with meningitis and septicemia, is indisputable. Various methods have been employed for this purpose. Each has advantages and disadvantages. This report describes a modification of the capillary acidometric procedure in which an agar plate is substituted for a tube. All beta-lactamase results obtained by this modified technique correlated with minimal inhibitory concentrations determined in liquid media and the chromogenic cephalosporin substrate method. This modified acidometric agar procedure is a simple, inexpensive, accurate, and rapid way to determine H. influenzae susceptibility to ampicillin.